Water Pollution Levels Based on Organic Matter Parameters and Amount of Escherichia coli Bacteria in the Mosque River Estuary of Dumai City - Abmi, Cyndy; Nedi, Syahril; Effendi, Irwan (Journal of Coastal and Ocean Sciences, 2021)
This research was conducted in March 2020 at Mosque River Estuary of Dumai City, Riau Province. The aimed of this research was to determine the pollution levels in the Mosque River Estuary based on organic matter parameters and E. coli bacteria. DO analysis refers to SNI 06.6989.14-2004, BOD5 refers to SNI 06-2503-2009, BOT refers to SNI 06-6989.22-2004 and E. coli bacteria refers to SNI 2897: 2008. The results of DO measurements ranged from 5.30 - 5.56 mg/l, BOD5 ranged from 16.5-21.8 mg/l, BOT ranged from 15 - 162 mg/l, and bacteria E. coli ranges from 11.1 - 1,100 MPN/100ml. Based on the results of the account of the Pollution Index, the Mosque River Estuary waters of Dumai City, Riau Province, are categorized as light to moderate pollution.